Modeling chemistry in and above snow at Summit, Greenland - Part 1: Model description and results - Thomas, Jennie L.; Stutz, Jochen; Lefer, Barry; Huey, L.,; Toyota, K.; Dibb, Jack,; von Glasow, Roland (Atmospheric Chemistry and Physics, 2011)
International audience Sun-lit snow is increasingly recognized as a chemical reactor that plays an active role in uptake, transformation, and release of atmospheric trace gases. Snow is known to influence boundary layer air on a local scale, and given the large global surface coverage of snow may also be significant on regional and global scales. We present a new detailed one-dimensional snow chemistry module that has been coupled to the 1-D atmospheric boundary layer model MISTRA. The new 1-D snow module, which is dynamically coupled to the overlaying atmospheric model, includes heat transport in the snowpack, molecular diffusion, and wind pumping of gases in the interstitial air. The model includes gas phase chemical reactions both in the interstitial air and the atmosphere. Heterogeneous and multiphase chemistry on atmospheric aerosol is considered explicitly. The chemical interaction of interstitial air with snow grains is simulated assuming chemistry in a liquid-like layer (LLL) on the grain surface. The coupled model, referred to as MISTRA-SNOW, was used to investigate snow as the source of nitrogen oxides (NOx) and gas phase reactive bromine in the atmospheric boundary layer in the remote snow covered Arctic (over the Greenland ice sheet) as well as to investigate the link between halogen cycling and ozone depletion that has been observed in interstitial air. The model is validated using data taken 10 June-13 June, 2008 as part of the Greenland Summit Halogen-HOx experiment (GSHOX). The model predicts that reactions involving bromide and nitrate impurities in the surface snow can sustain atmospheric NO and BrO mixing ratios measured at Summit, Greenland during this period.